ON SOME ISSUES OF IMPOSING A MONETARY PENALTY IN CRIMINAL PROCEEDINGS - Smyshlyaev Александр Сергеевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
This article discusses the imposition of financial penalties in the criminal process under the new criminal-procedural legislation of the Republic of Kazakhstan. The author suggests measures to improve procedural order imposing monetary penalties